Role of educational science teachers - De Hernandez, Mercedes (Revista Universidad de Guayaquil, 1983)
In order to analyze the problems of higher education and the tasks of the Edu supe Science teachers, it is necessary to make some considerations regarding the characteristics of educational systems, the changes they have experienced, the training of teachers and study plans of the Faculties of Education, as well as the peculiarities of the university level.